If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 = -2(-8 + -7a) 86 = (-8 * -2 + -7a * -2) 86 = (16 + 14a) Solving 86 = 16 + 14a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14a' to each side of the equation. 86 + -14a = 16 + 14a + -14a Combine like terms: 14a + -14a = 0 86 + -14a = 16 + 0 86 + -14a = 16 Add '-86' to each side of the equation. 86 + -86 + -14a = 16 + -86 Combine like terms: 86 + -86 = 0 0 + -14a = 16 + -86 -14a = 16 + -86 Combine like terms: 16 + -86 = -70 -14a = -70 Divide each side by '-14'. a = 5 Simplifying a = 5
| -3p+3=7x+1 | | 8(5-2n)=88 | | (1/2)x-(1/3)x=5 | | 4(-6x+6)=24 | | 8x^2=600 | | 8x^2=400 | | -113=-x+6(-6+2x) | | m+18=19 | | 3x+4-12x-3=9x+1 | | 5(8+2k)=100 | | X^2=48-14x | | 77y=38(2y+3) | | (x+6)(x-7)(x-12)=0 | | 6=2r+4r | | -x^2-12x+3=0 | | -3=v-2-5 | | 10x-39+12x-9x+42-4x=42+4x | | -7x+4+6x=5 | | 12=t-6 | | X+32-2x+34= | | 2x+x=17 | | -19=9v+8 | | 6y=-9x+-42 | | 5m^3-4m^2+9m-7= | | x+5+5= | | 2(m-3)+6=-3(m+1) | | 2(k-4)=-34 | | 8x+2=2(4x+1) | | 11+k=25 | | 11=3a+5 | | 4m-3=53 | | 8+4x=8x+24-12 |